Comments from the Project Launch: A Summary of Next Steps for CCAFS - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
Interview with CGIAR Climate Program Director Bruce Campbell. Mr Campbell talks about the future for CCAFS and what steps to take. Filmed at The Conference on Climate Change, Agriculture, and Food Security, 4 May 2010, Nairobi, Kenya